EBG antenna design - Ma, Xinqi (2015)
This project investigates the effects of electromagnetic band gap (EBG) structures on the performance of the rectangular microstrip antenna. The EBG ground plane is achieved by etching certain shape of cavities periodically on the ground plane beneath the patch. By loading the EBG structure, a band gap can be created for frequencies around the operation frequency of antenna. With such properties, EBG structure helps to improve the performances of a microstrip antenna in term of cross polarization suppression, radiation pattern, bandwidth and realized gain. Moreover, the effect of size reduction of the patch is an important advantage of loading EBG structure as well. In this report, four compact microstrip antenna structures are designed, which are loaded with the hole EBG, the cross EBG, the star shaped EBG, and Square Sierpinski Fractal EBG, respectively. In order to compare their dimensions and operating properties, they are all tuned to work at 2.4 GHz, and all use the same dielectric material (FR-4). These four antennas are fabricated and measured. All the four EBG antennas have shown a significant improvement in terms of harmonics suppression, gain and bandwidth enhancement and size reduction. The measured results agree well with the simulated ones.